Insight into the Role of Long Non-coding RNAs During Osteogenesis in Mesenchymal Stem Cells - Huo, Sibei; Zhou, Yachuan; He, Xinyu; Wan, Mian; Du, Wei; Xu, Xin; Ye, Ling; Zhou, Xuedong; Zheng, Liwei (Current Stem Cell Research & Therapy, 2018)
Background: Long non-coding RNAs (LncRNAs) are non-protein coding transcripts longer than 200 nucleotides in length. Instead of being “transcriptional noise”, lncRNAs are emerging as a key modulator in various biological processes and disease development. Mesenchymal stem cells can be isolated from various adult tissues, such as bone marrow and dental tissues. The differentiation processes into multiple lineages, such as osteogenic differentiation, are precisely orchestrated by molecular signals in both genetic and epigenetic ways. Recently, several lines of evidence suggested the role of lncRNAs participating in cell differentiation through the regulation of gene transcriptions. And the involvement of lncRNAs may be associated with initiation and progression of mesenchymal stem cell-related diseases. Objective: We aimed at addressing the role of lncRNAs in the regulation of osteogenesis of mesenchymal stem cells derived from bone marrow and dental tissues, and discussing the potential utility of lncRNAs as biomarkers and therapeutic targets for mesenchymal stem cell-related diseases. Results: Numerous lncRNAs were differentially expressed during osteogenesis or odontogenesis of mesenchymal stem cells, and some of them were confirmed to be able to regulate the differentiation processes through the modifications of chromatin, transcriptional and post-transcriptional processes. LncRNAs were also associated with some diseases related with pathologic differentiation of mesenchymal stem cells. Conclusion: LncRNAs involve in the osteogenic differentiation of bone marrow and dental tissuederived mesenchymal stem cells, and they could become promising therapeutic targets and prognosis parameters. However, the mechanisms of the role of lncRNAs are still enigmatic and require further investigation.
Keywords: osteogenesis